2002
DOI: 10.1002/app.11365
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on poly(propylene) (PP)/ethylene–vinyl acetate copolymer (EVA) blends

Abstract: Radiation effects on poly(propylene)/ethylene-vinyl acetate copolymer (PP/EVA) blends are discussed. Increasing the EVA content enhanced the crosslinking effect of radiation in PP/EVA blends. This effect was significant when the EVA content was Ն50% in PP/EVA blends that were exposed to ␥-ray irradiation in air. This phenomenon is discussed in relation to the compatibility, morphology, and thermal properties of PP/EVA blends. The results indicate that the effect is dependent on the compatibility, the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…Nevertheless, the nanocomposites obtained using the masterbatch clay introduction strategy presented different morphologies as a function of the PP/EVA concentration ratio. Figure (b) presents the irregularly joined droplet morphology of the EVA phase dispersed into the continuous PP phase for the PPEVA2MB sample, previously observed in Figure (a) . The reaction of PP and EVA using DCP and the previous introduction of nanoclay into the EVA matrix (masterbatch) caused the joined anisotropic morphology for this nanocomposite.…”
Section: Resultssupporting
confidence: 52%
“…Nevertheless, the nanocomposites obtained using the masterbatch clay introduction strategy presented different morphologies as a function of the PP/EVA concentration ratio. Figure (b) presents the irregularly joined droplet morphology of the EVA phase dispersed into the continuous PP phase for the PPEVA2MB sample, previously observed in Figure (a) . The reaction of PP and EVA using DCP and the previous introduction of nanoclay into the EVA matrix (masterbatch) caused the joined anisotropic morphology for this nanocomposite.…”
Section: Resultssupporting
confidence: 52%
“…Other parameters can modify the efficiency of irradiation, such as the compatibility of polymers,12 the atmosphere,13 the radiation rate and the total dose. For example, Miguez Suarez et al10 have shown that LDPE undergoes crosslinking reactions at low doses but chain scissions at high doses.…”
Section: Introductionmentioning
confidence: 99%
“…The higher mobile methyl radicals in PVA chains combined with alkyl radicals in PP chains can enhance cross-linking in PP=EVA blend. So that the cross-linking in PP=EVA blend was enhanced by alkyl radicals in PP chains and methyl radicals in EVA chains [9] . Along with alkyl radicals, the possibility of formation of vinylidene in PP segments also enhances the cross-linking [21] .…”
Section: Results and Discussion Chemical Analysismentioning
confidence: 99%
“…However, the radiation cross-linking efficiency of PP is lowered because of its tendency to undergo chain-scission and easy oxidation by irradiation in air. But both alkyl radicals in PE chains and methyl radicals in PVA chains participate in the radiation cross-linking of EVA (EVA is a block copolymer consists of the chains in PE and PVA) [9] .…”
Section: Results and Discussion Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation